Response of Wheat to Cycocel Application - I. Effects of nitrogen level and CCC concentration on plant height of dwarf and tall wheat. - El-SHARKAWY, M. A.; SGAIER, K.; RAMADAN, M. M. (The Libyan Journal of Agriculture, 2023)
The effect of nitrogen fertilizer at the rate of 40, 80 and 120 kg/ha and the foliar spray of the growth retardant, cycocel, at a rate of 0,2.5,6.0 kg/ha a.i. on the plant height was studied using the dwarf variety Sidi Misri ‘1’ and the tall variety Florence aurora; CCC strongly reduced plant height of the Florence aurora variety with an average reduction of 10 and 9 cm at 2.5 and 6.0 kg/ha a.i. respectively, whereas Sidi Misri ‘1’ did not respond to CCC application even at the highest concentration used. Nitrogen application significantly increased stem height of Sidi Misri ‘1’ while Florence aurora was not affected. Also there were significant variety x cycocel and variety x cycocel x nitrogen interactions.